Vena Cava Filters and In-Hospital Case Fatality Among Patients With Pulmonary Embolism: Results From a Large Population-Based Study - Pomero, Fulvio (Clin Appl Thromb Hemost, 2019)
In patients with venous thromboembolism (VTE), vena cava filters (VCFs) are currently only recommended when anticoagulant treatment is contraindicated or if VTE has recurred despite adequate anticoagulation. However, evidence on the efficacy of filter in patients with VTE is not compelling. We evaluated potential efficacy of VCF in reducing in-hospital mortality in a large population of patients presenting with a first episode of pulmonary embolism (PE). Patients were collected using regional hospital-discharge databases covering a population of more than 13 million of inhabitants in Northern Italy. For each year of observation, we calculated the proportion of cases with VCF among all PE incident cases. The temporal trend of VCF application during the study period was also derived. The effect of VCF use on in-hospital case-fatality rate was evaluated with a multivariate regression model and with the use of propensity score matching. During the study period (2002-2012), 60 813 patients were hospitalized for a first episode of acute PE. In-hospital case-fatality rate for PE was 13.3%. Vena cava filters were used in 745 (1.22%) patients. The annual use of VCF remained stable from 2002 to 2008, while it progressively decreased afterward. After adjustment for available confounders, case-fatality rate remained significantly lower in patients who received VCF compared to the one registered in patients who did not (odds ratio [OR] 0.46; 95% confidence interval [CI]: 0.34-0.62). Propensity score matching gave similar results (OR: 0.42; 95% CI: 0.30-0.61). Vena cava filters were infrequently used in patients with acute PE. Insertion of VCF appeared to sensibly reduce all-cause in-hospital mortality in this subgroup of patients.